Occurrence of a mosaic virus disease on sunflower in Karnataka - S.J. SINGH1; K. VIRUPAKSHAPPA1, NAGARAJU, V. MUNIYAPPA (Indian Phytopathology, 2002)
In Bangalore, India, a virus disease of sunflower producing chlorotic ringspot and mosaic symptoms was found to be transmitted by mechanical sap inoculation (up to 40%) and by Aphis gossypii (20-24%), A. craccivora (14-16%) and Myzus persicae (20-25%) to the sunflower cultivars Morden and KBSH 1. The virus had a very narrow host range infecting only 1 weed host, Galinsoga parviflora, a dilution end point of 1:500-1:1000, a thermal inactivation point of 55-65deg C and longevity in vitro for 66-72h at room temperature (21-28deg C). The virus particles could not be observed under the electron microscope, both with purified preparations and ultrathin sections of infected sunflower leaf samples. The virus is being considered as sunflower mosaic virus, hitherto unreported from Karnataka.